Prevalence and Pregnancy Outcomes of Intrahepatic Cholestasis of Pregnancy - Sitaula, Deekshanta; Timalsina, Santosh; Sharma, Basant; Pokharel, Bandana; Thapa, Rohit (Journal of Nepal Health Research Council, 2021)
Background: Intrahepatic cholestasis of pregnancy is a common pregnancy-specific liver disease associated with increased risk of adverse fetal and maternal outcomes. We sought to determine its prevalence, risk factors and feto-maternal outcomes. Methods: A retrospective review of data of 164 pregnant women diagnosed with intrahepatic cholestasis of pregnancy at Chitwan Medical College, Nepal from August 2018 to September 2020 was done. Socio-demographic data, clinic-laboratory profile and feto-maternal outcomes were obtained from clinical audit books and electronic records. A multivariate logistic regression analysis was used to evaluate the predictors of adverse neonatal outcome. Results: The prevalence of intrahepatic cholestasis of pregnancy was 2.5% (164 out of 6539 deliveries). The mean age was 27.5 ± 4.4 years and 51.2% were multigravida. The preterm delivery rate was 15.2% and Caesarean delivery rate was 69.5%. 22% of the neonates needed intensive care admission out of which Respiratory Distress Syndrome or Transient Tachypnea of Newborn was seen in half of them. There were 2 cases of Intrauterine Fetal Death. In multivariate analysis, delivery <34 weeks of gestation was only found to be a significant independent predictor of adverse neonatal outcome Conclusion: The prevalence of intrahepatic cholestasis of pregnancy among pregnant women is significant in our setting which is associated with adverse fetal outcome. Early diagnosis and timely intervention is necessary in order to reduce associated perinatal morbidity. Keywords: Intrahepatic cholestasis of pregnancy; liver function tests; neonatal outcome; obstetric cholestasis